A national survey of nurse-led and delivered services within sexual health across the United Kingdom. (October 2016) - Wiggins, H; Kell, P; Joshi, U; Rajamanoharan, S; ,
This was a cross-sectional study using an online survey to evaluate the provision of nurse-led and delivered services within genitourinary medicine in the UK. Results showed that such services are being widely utilised and are generally well supported by medical staff. The delivery of nurse-led and delivered services appears to be quite variable. Clinical guidelines and standards may help to ensure a more uniform approach to these services and help to maintain high standards of care.